Association between admission serum potassium concentration and the island sign on cranial CT in HICH patients: a cross-sectional study - Wang, Yanglingxi; Chen, Peng; Liang, Yidan; Deng, Yongbing; Zhou, Weiduo (Frontiers in Neurology, 2024)
Objective: Investigate the relationship between admission serum potassium (K+) levels and the Island Sign (IS) presence in Hypertensive Intracerebral Hemorrhage (HICH) patients' cranial CT scans, considering potential non-linear patterns. Methods: Analyzed data from 330 HICH patients, using logistic regression and curve-fitting models to explore associations. Results: Discovered a non-linear correlation, with an inflection point at approximately 3.54 mmol/L. Lower serum K+ levels upon admission associated with higher IS incidence. Conclusions: Suggests maintaining physiological serum K+ levels may mitigate IS risk in HICH patients, highlighting its potential significance.